2022
DOI: 10.7759/cureus.21256
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Health Interventions on Antenatal and Postnatal Care Utilization in Low- and Middle-Income Countries: A Meta-Analysis

Abstract: Despite many efforts, the utilization of full antenatal and postnatal care remains a significant concern in low-and middle-income countries (LMICs). We planned to retrieve the relevant literature and pooled the data for meta-analysis to evaluate the impact of mobile health (mHealth) intervention on antenatal and postnatal care utilization in low-and middle-income countries. We searched the literature through major electronic databases such as PubMed, MEDLINE, Embase, Cochrane, Scopus, CINAHL, Clinical key, Goo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In terms of mHealth functions, we observed that all 12 functions of mHealth described by Labrique et al [ 163 ] was used in the reviewed articles. The most frequently used function among the reviewed studies by far was “client education and BCC” (mHealth Function 1), as seen in past reviews [ 22 , 164 , 167 ], providing relevant information and reminders for ANC/PNC appointments, childbirth, immunization, and breastfeeding, which had the advantage of simplicity, feasibility, and achievability.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mHealth functions, we observed that all 12 functions of mHealth described by Labrique et al [ 163 ] was used in the reviewed articles. The most frequently used function among the reviewed studies by far was “client education and BCC” (mHealth Function 1), as seen in past reviews [ 22 , 164 , 167 ], providing relevant information and reminders for ANC/PNC appointments, childbirth, immunization, and breastfeeding, which had the advantage of simplicity, feasibility, and achievability.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that technology support can improve maternal and child health especially, in highly affected regions such as sub-Saharan Africa, and as there is an adequate number of mothers who can use mobile phones [ 11 , 12 ]. It is a promising advance in LMIC, especially when it has health professionals’ support and beliefs [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate antenatal care is imperative for the delivery of a healthy baby to a healthy mother and to lessen maternal and neonatal morbidity and mortality. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%